New modes of governance in Europe: Policy-making without legislating? - Adrienne Héritier (Max-Planck-Projektgruppe Recht der Gemeinschaftsgüter, 2001)
The focus of this analysis is on new modes of governance and government in the European Union that (a) include private actors in policy formulation, and/or (b) while being based on public actors, (c) are only marginally based on legislation (these are hierarchical insofar as they are subject to a majority decision) or that are not based on legislation at all. In recent years non-legislative modes of policy-making and modes of governance including private actors in policy-formulation have gained in salience in European policy-making, and they have been advocated as a panacea for speeding up European decision making, which has so often ended up in gridlocks (Héritier 1999). The European integration project has reached a stage where core areas of the welfare state such as employment policy, social policy, and education are directly affected. These are areas where member state political support is very difficult to gain (Jacobsson 2001). Hence a method of cooperation has been developed to avoid the classical form of legislation through directives and regulations; instead, it relies on the open method of coordination, that is, target development and published scoreboards of national performance, as measured by the policy objectives that have been agreed upon, as well as voluntary accords, that is, the self-regulation of private actors.
Keywords: 330